Developing Religious Thinking Using C. S. Lewis’s Chronicles of Narnia - Dana Hanesová; Pavel Hanes; Daniela Masariková (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The authors present the results of authentic theologizing with children while using the Chronicles of Narnia by C. S. Lewis in the process of religious education. Since the 1950s, when this series of seven fantasy novels for children was published it became recognized as an English classic of children’s literature. Although from the beginning, they have faced praise as well as criticism – particularly due to the recent attempt to use them as a script for a film adaptation – experience with this series of children’s book shows that they can contribute positively to the development of children’s religious thinking. The most important concept for the development of the spirituality of children is their concept of God and what it means to have faith in God.